Trabajadores, empresarios y estado: la dinámica de clases y los límites institucionales del conflicto. 1900-1943 - Hernández Rodríguez, Carlos (1993)
This article explores relations among workers, employers and the State during the years 1900 to 1943. The author reconstructs the institutional framework within which collisions and negotiations among the parties involved occurred. He also characterizes the transition process which led to a mew order in terms of labor relations and social reforms of the 1940s.